2019
DOI: 10.1111/jcmm.14466
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Wine Polyphenolic Compounds prevents Doxorubicin‐induced cardiotoxicity through activation of the Nrf2 signalling pathway

Abstract: Doxorubicin (DOX) is considered as the major culprit in chemotherapy‐induced cardiotoxicity. Yellow wine polyphenolic compounds (YWPC), which are full of polyphenols, have beneficial effects on cardiovascular disease. However, their role in DOX‐induced cardiotoxicity is poorly understood. Due to their antioxidant property, we have been suggested that YWPC could prevent DOX‐induced cardiotoxicity. In this study, we found that YWPC treatment (30 mg/kg/day) significantly improved DOX‐induced cardiac hypertrophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…Several plant-derived polyphenols have drawn attention in pharmaceutical field thanks to their ability to reduce oxidation species synthesis and accumulation in human body [ 5 , 20 , 21 , 52 , 53 ]. Recently, it was reported that curcumin is able to ameliorate the doxo cardiotoxic effect in vitro and in vivo [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several plant-derived polyphenols have drawn attention in pharmaceutical field thanks to their ability to reduce oxidation species synthesis and accumulation in human body [ 5 , 20 , 21 , 52 , 53 ]. Recently, it was reported that curcumin is able to ameliorate the doxo cardiotoxic effect in vitro and in vivo [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a concomitant reduction in anti-cancer efficacy and side effects intensification have radically hampered the following clinical trials investigation [ 18 , 19 ]. Recently, due to their well-known antioxidant properties, many attentions have been paid to the plant-derived polyphenols as a possible strategy in the prevention of doxo-induced cardiotoxicity [ 5 , 20 , 21 ]. Speaking of which, it has been reported that curcumin, a natural phenol abundant in turmeric, is able to ameliorate the doxo-induced cardiotoxic effect both in vitro and in vivo studies [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor-like 2 (Nrf2) is an important member of the cap collar family of basic leucine zipper transcription factors; it plays a role in the antioxidant defense system by regulating the expression of antioxidant enzymes [ 17 , 18 ]. During conditions of oxidative stress, Nrf2 is activated, translocated to the nuclear region, and combined with the antioxidant response element located in the promoter region of phase II antioxidant enzyme genes, such as heme oxygenase 1 ( HO-1 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that NRF2 is involved in the LXA4-induced reduction in the level of inflammatory factors. [173] and Hiebert et al [52]).…”
Section: Connection Between Nrf2 and Lxsmentioning
confidence: 94%
“…LXA4 can activate NRF2 by inducing the phosphorylation of Ser40 of NRF2 to induce nuclear translocation. Phosphorylated NRF2 can form a heterodimer with sMAF and bind to ARE, leading to the transcription of antioxidant genes, such as HO-1, NQO-1, SOD, and TXN (modified from Lin et al [ 173 ] and Hiebert et al [ 52 ]).…”
Section: Figurementioning
confidence: 99%